A Comprehensive Strategy Based on UPLC-Q/TOF-MS for the Identification of Compounds in a Chinese Patent Medicine, Xiao'er Chiqiao Qingre Granules. (3rd April 2022) - Tian, Gang; Gao, Mengting; Li, Chao; Shen, Fei; Zhu, Feng; Li, Xin; Wang, Yifei; Bao, Beihua; Zhang, Li; Huo, Zongli; Yao, Weifeng
Abstract: The aim of this study was to establish a comprehensive strategy based on liquid chromatography coupled with mass spectrometry to potently identify as many compounds of Chinese patent medicine as possible. Ultrahigh performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF-MS) was used to qualitatively analyze the Chinese patent medicine Xiao'er Chiqiao Qingre Granules (XCQG), which is recorded in the Chinese Pharmacopoeia. A novel strategy, including targeted, semi-targeted and non-targeted identification, was built to explore the compounds based on accurate mass, characteristic fragments, retention time of standard substances, databases or literature. Based on the integrated identification, 250 compounds were identified in total, including 7 alcohols, 3 aldehydes, 17 alkaloids, 9 amino acids, 10 coumarins, 30 flavonoids, 29 glycosides, 12 ketones, 7 lignans, 20 organic acids, 12 phenols, 11 phenylpropanoids, 9 quinones, 3 steroids, 26 terpenes, 14 volatile oils and 31 other compounds. A novel strategy for the identification of compounds in traditional Chinese medicine (TCM) was developed with Ultrahigh performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF-MS). It is also the first systematic study of compounds in XCQG, laying a foundation for further mechanism research of XCQG. More importantly, the strategy shows good application prospect in identifying compounds of TCM.